Ecogothic - Smith, Andrew, 1964-; Hughes, William, 1964- (International Gothic (Manchester, England), 2013)
This book will provide the first study of how the Gothic engages with ecocritical ideas. The book's focus is from the late eighteenth century to the present day, via consideration of a number of national and global contexts and different media including short stories, novels and films.